Gestational and Early Postnatal Exposure to an Environmentally Relevant Mixture of Brominated Flame Retardants: General Toxicity and Skeletal Variations. Issue 3 (10th June 2016) - Tung, Emily W. Y.; Yan, Han; Lefèvre, Pavine L. C.; Berger, Robert G.; Rawn, Dorothea F. K.; Gaertner, Dean W.; Kawata, Alice; Rigden, Marc; Robaire, Bernard; Hales, Barbara F.; Wade, Michael G.
Abstract : Brominated flame retardants (BFRs) are stable environmental contaminants known to exert endocrine‐disrupting effects. Developmental exposure to polybrominated diphenyl ethers (PBDEs) is correlated with impaired thyroid hormone signaling, as well as estrogenic and anti‐androgenic effects. As previous studies have focused on a single congener or technical mixture, the purpose of the current study was to examine the effects of gestational and early postnatal exposure to an environmentally relevant mixture of BFRs designed to reflect house dust levels of PBDEs and hexabromocyclododecane on postnatal developmental outcomes. Pregnant Sprague‐Dawley rats were exposed to the PBDE mixture from preconception to weaning (PND 21) through the diet containing 0, 0.75, 250, and 750 mg mixture/kg diet. BFR exposure induced transient reductions in body weight at PND 35 in male and from PND 30–45 in female offspring (250 and 750 mg/kg). Liver weights (PND 21) and xenobiotic metabolizing enzyme activities (PND 21 and 46) were increased in both male and female offspring exposed to 250 and 750 mg/kg diets. Furthermore, serum T4 levels were reduced at PND 21 in both, male and female offspring (250 and 750 mg/kg). At PND 21, Serum alkaline phosphatase (ALP) was decreased in males exposed to 750 mg/kg dietat, and females exposed to 250 and 750 mg/kg diets. At PND 46 ALP was significantly elevated in males (250 and 750 mg/kg). Variations in the cervical vertebrae and phalanges were observed in pups at PND 4 (250 and 750 mg/kg). Therefore, BFR exposure during gestation through to weaning alters developmental programming in the offspring. The persistence of BFRs in the environment remains a cause for concern with regards to developmental toxicity